Pembuatan Dendeng Analog Dengan Penambahan Tepung Tempe Kedelai Hitam Sebagai Olahan Pangan Tinggi Protein - Dyvia Agustina Sidup; Reza Fadhilla; Prita Dhyani Swamilaksita; Mertien Sa'pang; Dudung Angkasa (Universitas Muhammadiyah Semarang, 2022)
One of the problems arising from overconsumption of meat is degenerative diseases and many people are turning to vegetarianism. Vegetarians tend to experience protein deficiency problems, therefore one of the most popular food preparations for the community and have high nutritional value is making jerky analogue of banana hearts with the addition of black soybean tempeh flour. To analyze differences in nutrient content and acceptability (color, taste, aroma and texture) with the addition of black soybean tempe flour. This type of research is an experimental study, there are 4 formulations with a ratio of black soybean tempeh flour banana heart and in analog jerky, namely F0 (100%), F1 (15%: 85%), F2 (20%: 80%), F3 (25%: 75%). The Nutritional Testing which was conducted was the analysis of proximate levels and crude fiber content. Organoleptic assessment uses a Likert form with a scale of 1-5 against 50 consumer panelists. Based on the assessment of the results of nutrition and consumer panelists, the selected formulations were F3 with 27.24 g protein, 11.23 g fat, 22 g carbohydrates, 5.71 g crude fiber content, 36.05 g moisture content and ash content 3.46 g. There is an effect of adding black soybean tempe flour to the nutritional value of analog jerky. There is a significant difference in the acceptability of texture and taste in analog jerky.